Genetic Variations and Antibiotic-Related Adverse Events - Nicola Principi; Kyriakoula Petropulacos; Susanna Esposito (MDPI AG, 2024)
Antibiotic-related adverse events are common in both adults and children, and knowledge of the factors that favor the development of antibiotic-related adverse events is essential to limit their occurrence and severity. Genetics can condition the development of antibiotic-related adverse events, and the screening of patients with supposed or demonstrated specific genetic mutations may reduce drug-related adverse events. This narrative review discusses which genetic variations may influence the risk of antibiotic-related adverse events and which conclusions can be applied to clinical practice. An analysis of the literature showed that defined associations between genetic variations and specific adverse events are very few and that, at the moment, none of them have led to the implementation of a systematic screening process for patients that must be treated with a given antibiotic in order to select those at risk of specific adverse events. On the other hand, in most of the cases, more than one variation is implicated in the determination of adverse events, and this can be a limitation in planning a systematic screening. Moreover, presently, the methods used to establish whether a patient carries a "dangerous" genetic mutation require too much time and waiting for the result of the test can be deleterious for those patients urgently requiring therapy. Further studies are needed to definitively confirm which genetic variations are responsible for an increased risk of a well-defined adverse event.